Horticultural subsectors in Grenada, Guyana, Jamaica, Montserrat and St Kitts/Nevis/Anguilla (Stevenson & Kellog Management Consultants TorontoCA, 1980)
Describes the horticultural subsector in Grenada, Guyana, Jamaica, Montserrat, and St Kitts/Nevis. For each subsector describes the institutional environment within which the horticultural production, distribution and marketing systems operate. Also describes the production, marketing, handling and transporting, and processing of horticultural products.
Project report